(untitled) (Journal of Atomic and Molecular Sciences, 2016)
The photodetachment cross section of H^- near two perpendicular elastic planes is investigated in this paper. Both the traditional quantum approach and closed orbit theory are applied to explicitly derive the formulas of the cross section for different laser polarization direction. We first compared the quantum formulas with closed orbit theory formulas, and then found that the quantum results are shown to be in good agreement with the semiclassical results. Furthermore, we also found that the cross section depends strongly on the direction of the laser polarization. When the polarization is parallel to the closed orbit, the corresponding oscillation in the cross section is very obvious. However, When the polarization is perpendicular to the closed orbit, the corresponding oscillation is too small for closed-orbit theory formula to describe.